Farm-based measures for reducing microbiological health risks for consumers from informal wastewater-irrigated agriculture - Keraita, Bernard N.; Konradsen, Flemming; Drechsel, Pay (2010)
This chapter presents farm-based measures that have been developed and tested in the informal irrigation sector to reduce microbiological health risks for consumers from wastewater irrigation of vegetables commonly eaten uncooked. The measures target poor smallholder farmers or farmer associations in developing countries as part of a multiple-barrier approach for health-risk reduction along the farm to fork pathway. Measures discussed include treatment of irrigation water using ponds, filters and wetland systems; water application techniques; irrigation scheduling; and crop selection. In addition, the chapter highlights some practical strategies to implement these measures, based largely on field experiences in Ghana. Although most measures discussed do not fully eliminate possible health risks, they can significantly complement other pathogen barriers. Which measures fit, either alone or in combination, will depend on local site characteristics and practices. Further studies are required to develop new measures or adapt them to other irrigation practices and systems in developing countries.